(untitled) (Altre Modernità, 2015)
Lev Kopelev grew up and studied during Stalinism, when a progressive closure towards the West characterized Eastern countries. Nevertheless, thanks to different inputs he received as a young man, he underwent a path of personal growth, which led him to develop a project of dialogue and openness towards the “other”. Surrounded by the cosmopolitan atmosphere of Kiev at the beginning of the XX century, he learned German as child, and kept researching an open dialogue with the German people, which reached his peak in the Eighties, after he was deprived of the Soviet citizenship and became a citizen of the Federal Republic of Germany. Germanist by profession, he dedicated his life to the in depth examination of the links between Russians and Germans towards the centuries, and got to formulate the theory of a spiritual “elective affinity” between the two nations. His research led to a great project: the “Wuppertaler Projekt zur Erforschung der Geschichte Deutsch-Russischer Fremdenbilder”. In this work Kopelev firstly analysed the evolution of the relationship between the two nations from a literary, political, social and cultural point of view, and, secondly, examined the genesis and the development of the prejudices of the Germans towards the Russians and vice versa. The work showed the intrinsic groundlessness of these prejudices and offered the two nations the possibility of observing and understanding a different reality.